2014
DOI: 10.1161/hypertensionaha.113.02619
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Protects Against Systolic Overload–Induced Heart Failure Independent of AMP-Activated Protein Kinase α2

Abstract: Activation of AMP-activated protein kinase (AMPK) α2 protects the heart against pressure overload-induced heart failure in mice. Although metformin is a known activator of AMPK, it is unclear whether its cardio-protection acts independently of an AMPKα2-dependent pathway. Because the role of AMPKα1 stimulation on remodeling of failing hearts is poorly defined, we first studied the effects of disruption of both the AMPKα1 and AMPKα2 genes on the response to transverse aortic constriction (TAC)-induced left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 28 publications
4
40
0
1
Order By: Relevance
“…In addition to changes in transcript levels of stress genes associated with HF and HF regression, previous reports have demonstrated TAC-induced activation of Akt and the mTOR signalling pathway. 24 While expression of phosphorylated proteins did not appear to be altered in our HF mice (data not shown), total protein levels of Akt, mTOR, Raptor, 4E-BP1, S6, and GSK3b were significantly increased in response to pressure-overload, as previously described. 25 More importantly, we observed normalized cardiac content of these regulators of protein synthesis following DB ( Figure 2E and F ), suggesting that some of the molecular signalling events that control hypertrophic growth have returned to baseline values and that the pro-hypertrophic molecular stimuli have also regressed.…”
Section: Removal Of Elevated Aortic Afterload Causes a Regression Of supporting
confidence: 79%
“…In addition to changes in transcript levels of stress genes associated with HF and HF regression, previous reports have demonstrated TAC-induced activation of Akt and the mTOR signalling pathway. 24 While expression of phosphorylated proteins did not appear to be altered in our HF mice (data not shown), total protein levels of Akt, mTOR, Raptor, 4E-BP1, S6, and GSK3b were significantly increased in response to pressure-overload, as previously described. 25 More importantly, we observed normalized cardiac content of these regulators of protein synthesis following DB ( Figure 2E and F ), suggesting that some of the molecular signalling events that control hypertrophic growth have returned to baseline values and that the pro-hypertrophic molecular stimuli have also regressed.…”
Section: Removal Of Elevated Aortic Afterload Causes a Regression Of supporting
confidence: 79%
“…Subsequent studies also demonstrated that Met exerted its various effects, including cardioprotective effect through the activation of AMPK [ 22 24 ]. In contrast, recent studies showed that the blood glucose lowering effect, cardioprotective effect and anti-tumor effect of Met are all independent of AMPK [ 16 , 25 , 26 ]. Therefore, it is necessary to confirm whether the cardioprotective effect of Met during IR depends on AMPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies documented that the MET exerted cardioprotective effect via the activation of AMP activated protein kinase (AMPK) [ 10 , 14 , 15 ], whereas Xu et. al [ 16 ] reported that Met protected against systolic overload-induced heart failure independent of AMPK. In addition, Met has been shown to exhibit antioxidant properties in various disorders [ 17 , 18 ], we wonder whether the protective effect of Met against myocardial IR injury is through the elevation of endogenous antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Ampkα2 activation is protective in the failing heart [5]. Ampkα2-deficient mice, but not Ampkα1-deficient mice show dysfunctional expression of energy metabolism-related genes and exacerbated remodeling following TAC [65,66]. Therefore, the effects of Ampkα1 could be of significant importance especially in the failing heart.…”
Section: Discussionmentioning
confidence: 99%